Friendship and Personality Toward the Main Character in Wendy Mass’ The Candymakers - Mardiana Mardiana; Dahlia D. Moelier; Asyrafunnisa Asyrafunnisa (Humaniora: Journal of Linguistics, Literature, and Education, 2022)
The aims of the research are to find out the friendship and personality through the characters in the novel and to describe the impact of personality that affect their friendship towards the characters. The research applied the library research to get as many data from the novel and some books containing theories which connect to the research. The primary data was taken from The Candymakers by Wendy Mass. The writer used a qualitative descriptive research by using sociological approach and the theory of Aristotle for friendship and Neo-Freud’s theory of personality. The result shows the result of this study the types of friendship dominated by Virtuous/ Admiration because became a guide in made a friend. The types of personality in this study dominated by Aggressive personality but the impact that affect their friendship it would be Detached personality because solve the problem of friendship.